Impulsively Excited Nightside Ultralow Frequency Waves Simultaneously Observed on and off the Magnetic Equator - Kazue Takahashi; Richard E. Denton; Tetsuo Motoba; Ayako Matsuoka; Yasumasa Kasaba; Yoshiya Kasahara; Mariko Teramoto; Masafumi Shoji; Naoko Takahashi; Yoshizumi Miyoshi; Masahito Nosé; Atsushi Kumamoto; et al. (Geophysical Research Letters)
Abstract The Arase spacecraft is capable of observing ultralow frequency waves in the inner magnetosphere at intermediate magnetic latitudes, a region sparsely covered by previous spacecraft missions. We report a series of impulsively excited fundamental toroidal mode standing Alfvén waves in the midnight sector observed by Arase outside the plasmasphere at magnetic latitudes 13–24°. The wave onsets are concurrent with Pi2 onsets detected by the Van Allen Probe B spacecraft at the magnetic equator in the duskside plasmasphere and by ground magnetometers at low latitudes. The duration of each toroidal wave packet is ∼20 min, which is much longer than that of the corresponding Pi2 wave packet. The toroidal waves cannot be the source of high‐latitude Pi2 waves because they were not detected on the ground near the magnetic field footprint of Arase. Overall, the toroidal wave event lasted more than 2 hr and allowed us to use the wave frequency to estimate the plasma mass density at L = 6.1–8.3. The mass density (in amu/cm3) is higher than the electron density (cm−3) by a factor of ∼6, which implies that 17–33% of the ions were O+.